Tradisi Merariq dalam Kacamata Hukum Adat dan Hukum Islam - Fathul Hamdani; Ana Fauzia (Jurnal Hukum Lex Generalis, 2022)
One of the traditions that is still preserved by the Sasak people in Lombok is the Merariq (elopement) tradition. This tradition is a unique and distinctive tradition, because generally people consider elopement as a violation of customary laws, such as Batak, Balinese, Bugis, Makasar, Sumbawa and Mandar. The purpose of this study is to examine the relationship between customary law and Islamic Law, as well as how views on the Merariq tradition are viewed from the perspective of customary law and Islamic Law. The results of the study suggest that customary law and Islamic law complement each other without losing their respective identities. For example, before the Marriage Law came into force, in marriage for Muslims, the Islamic Marriage Law was a benchmark together with the Customary Marriage Law. Then regarding the Merariq tradition, it has actually been embraced by the Sasak tribe since ancient times. As for the process, the Merariq tradition also still refers to Islamic Law.